Dialysis dose in end-stage renal disease patients undergoing regular hemodialysis at Ibn-Sena and AlNao hospitals in Sudan - Essamaddin A Ibrahim (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Ne Hemodialysis (HD) plays a fundamental role in the treatment of end-stage renal disease (ESRD) patients. A minimal duration between 9 to 12 hours per week is required for maintaining adequate HD to restore excretory function of the kidney. Objectives: To measure the average duration of HD among Sudanese patients, and compare with the universal recommended duration. Patients and Methods: A cross-sectional, descriptive study at IBN-SENA hospital and ALNAO teaching hospital was conducted. All patients were subjected to full medical history and examination to identify their age, gender, original kidney disease and duration and route of HD. Results: A total of 121 ESRD patients under regular HD participated in this study. The majority [78 (64.5%)] had an average duration of HD of 8 h/wk. Conclusion: A large proportion of our patients on HD are below target dialysis dose; mainly due to reducing in the number of sessions per week and average duration per each session.